Identification of known and novel germ cell cancer‐specific (embryonic) miRs in serum by high‐throughput profiling. (7th November 2014) - Rijlaarsdam, M. A.; van Agthoven, T.; Gillis, A. J. M.; Patel, S.; Hayashibara, K.; Lee, K. Y.; Looijenga, L. H. J.
Summary microRNAs (miRs) are short non‐coding RNA molecules (≈21 nucleotides) involved in regulation of translation. As such they are crucial for normal cell development and differentiation as well as cellular maintenance. Dysregulation of miRs has been reported in various diseases, including cancer. Interestingly, miRs can be informative as tumor classifiers and disease biomarkers. Recent studies demonstrated the presence of miRs in body fluids like serum, thus providing a putative non‐invasive tool to study and monitor disease state. Earlier targeted studies by several independent groups identified specific embryonic miRs as characteristic for germ cell tumors (GCT) (miR‐371‐2‐3 & miR‐302/367 clusters). This study reports a high‐throughput miR profiling (≈750 miRs) approach on serum from testicular germ cell tumor patients (14 seminoma and 10 non‐seminoma) and controls (n = 11), aiming at independent identification of miRs as candidate biomarkers for testicular GCT. A magnetic bead capture system was used to isolate miRs from serum. Subsequently, the TaqMan Array Card 3.0 platform was used for profiling. The previously identified miRs 371 and 372 were confirmed to be specifically elevated in serum from germ cell tumor patients. In addition, several novels miRs were identified that were discriminative between germ cell cancer and controls: miR‐511, ‐26b, ‐769, ‐23a, ‐106b, ‐365, ‐598, ‐340, and let‐7a. In conclusion, this study validates the power of the embryonic miRs 371 and 372 in detecting malignant GCT (SE and NS) based on serum miR levels and identifies several potential novel miR targets.